Chemical and entropic control on the molecular self-assembly process - Daniel M. Packwood (Nature Portfolio, 2017)
Molecular self-assembly is controlled by chemical and entropic factors, but theory has not been able to differentiate the role of each. Here, the authors unambiguously address this question for self-assembly on metal surfaces, using a new computational method that bridges coarse-grained and atomistic approaches.